The role of microstructure on edge cracks in dual phase and quench and partitioning steels subject to severe cold rolling. (December 2019) - Samei, Javad; Salib, Youssef; Amirmaleki, Maedeh; Wilkinson, David S.
Abstract: Rolling edge cracks are characterized in a wide range of steels. Four different crack morphologies are identified. The propensity to cracking has an inverse relationship to the martensite content in dual phase steels, related to the interconnectivity of the martensite particles within the microstructure. An additional effect due to grain refinement is seen in dual phase steels which have the same martensite content but a factor of three difference in ferrite grain size. Quench and partitioning steels exhibit considerably lower resistance to edge cracking than dual phase steels due to the specific characteristics of the martensite in each steel. Graphical abstract: Unlabelled Image